PEMBANGUNAN EKONOMI BERBASIS SYARIAH - Rizal Fahlefi (JURIS (Jurnal Ilmiah Syariah), 2018)
Any decisions made on economy by human in Islam cannot be separated from moral and religious values since all activities upon economy are related to sharia (Islamic laws). Therefore, Islamic (sharia) economy is build upon fundamental values, whether in terms of philosophical, instrumental and institutional values as well, which are based on the Quran and the Sunnah (prophetic traditions). The developments of discourses on Islamic economy have been through long phases which finally promote the establishments of Islamic economy institutions to serve the Islamic (and non Islamic) communities (ummah). Due to the urgent needs of those institutions, the Indonesian government gave positive and serious responses by supporting various Islamic economy institutions to serve the Indonesian people who needs their services.